A straight line to my heart - Condon, Bill 1949- (Allen & Unwin, 2011)
School is out forever, and Tiff is hoping her job at the local paper will lead to something more ...But 'The Shark' soon puts her straight on what it takes to become a hard-nosed reporter like him. At home, Reggie - the only grandad she's ever known - has quit the smokes and diagnosed himself as cactus. Then her best friend, Kayla, hits her with some big news. And into all this stumbles Davey, the first boy who really wants to know her. Tiff is smart with words and rarely does tears, but in one short week she discovers that words don't always get you there and don't let you say all the stuff from deep in your heart